The Role Of Parents And Teachers In Forming The Culture Of Tolerance In Pupils Of General Education School - Abseit Trijanovich Rustemov (Euro Asian Journal Publishing, 2024)
The article is about tolerance education starting from every family and this is the main issue of today
Keywords: tolerance; family; child; school